STRUCTURE PROJECT APPLICATION PELAYANAN PASIEN RAWAT JALAN PADA RSIA SELARAS - Maimunah Maimunah; Septiyan Septiyan; Bayu Setiawan (Journal Cerita: Creative Education of Research in Information Technology and Artificial Informatics, 2016)
The need of information and services quickly, accurately, and satisfy the modern era like today, felt increasingly required by each agency. Especially RSIA Selaras engaged in health services and services at any time is always in touch with the community or customer. Problems that occur in the institution are particularly RSIA Selaras outpatient care system that is not good because it is still an error occurs in the search for patient data, preparation of reports, the accumulated cost of service and does not support the use of information technology in this case the client server. With the construction of the optimal system would minimize the problems that often occur in patient care and the system can run smoothly. Designing the information system of computerized patient care will be able to ensure the provision of time to generate information and can control the opinion of the hospital automatically because most of the data stored in the file as well as the support of the computerized system. Information system design services outpatient designed using Microsoft Visual Basic 6.0, using a MySQL database. It is expected the system he designed outpatient care information might help solve the problems faced RSIA Selaras. To obtain the data needed for the study, the authors used several methods, among others: interviews, observation, and literature. The data obtained and analyzed and described using UML (Unified Modeling Language), and design method by analyzing the running system to detect problems. Hence the need for a data processing and semi-manual system to a computerized data processing system by using a programming outpatient services in order to facilitate the process of outpatient services.